Reducing Call Drops Due to Cell Failure (International Journal of Engineering and Computer Science, 2017)
The dropped-call rate (DCR) is the fraction of the telephone calls which, due to technical reasons, were cut off before the speaking parties had finished their conversational tone and before one of them had hung up (dropped calls) This fraction is usually measured as a percentage of all .CDR is defined as the ratio of abnormal disconnect of calls to total calls established. The performance of a TSP relating to call drop is assessed through this parameter. The benchmark set by TRAI for CDR is